Hormone replacement therapy: a therapy of continuous controversies - M. Kanadys, Wiesław (Menopause Review/Przegląd Menopauzalny, 2004)
Since hormone replacement therapy (HRT) was introduced into practice, this therapy has had its followers as well as opponents, and it is still subject to discussion and controversy. During this time, the attitude to HRT was changing on a cyclical basis, from total approval to negation, depending on whether benefits surpass risks. After publishing the results of both Heart and Estrogen/progestin Replacement Study (HERS) and Women’s Health Initiative (WHI) trial a lively discussion is pending on HRT’s role in the prevention of cardiovascular diseases and generally on the legitimacy of its application. It is unquestionable that the main aim of HRT is to relieve climacteric symptoms which significantly affect the quality of life. But on the other hand, we cannot negate, basing on WHI and HERS trials, the results of studies that have been done so far showing that estrogen deficiency increases the progress of atherosclerosis and that postmenopausal estrogen replacement brings cardioprotective and neuroprotective effects. In spite of some reservations we must accept the results of WHI and HERS trials and recognize their importance, which will have an influence on our clinical procedure. We can argue about legitimacy of HRT administration basing on these or other studies or quoting scientific authorities, nevertheless, the choice of optimal management is made by an individual physician, and he must take into consideration, beside aliments of transitional period, all other circumstances such as the age, coexisting diseases, risk factors which can influence the effectiveness of hormonotherapy, and at last the response to HRT use which is still based to a large degree on the trial and error method.